Single-nucleotide polymorphisms within the BK polyomavirus non-coding control region are genotype-associated - Tiana A. Walder; Elizabeth A. Odegard; Heidi L. Meeds; Steven B. Kleiboeker; Assem Ziady; Anthony Sabulski; Sonata Jodele; Alix E. Seif; Stella M. Davies; Benjamin L. Laskin; Jason T. Blackard (Microbiology Spectrum)
ABSTRACT BK polyomavirus (BKPyV) is a non-enveloped, double-stranded, circular DNA virus that is a member of the Polyomaviridae family. The BKPyV genome is divided into three regions, including the non-coding control region (NCCR), the early region, and the late region. BKPyV has one of the highest mutation rates among DNA viruses, and four genotypes have been identified based on amino acid variation within the VP1 region. Mutations within the NCCR have been noted, and this region exhibits hypervariability. Here, we show that many of the point mutations observed within the NCCR are genotype-associated, termed genotype-associated polymorphisms (GAPs). These GAPs correlate with regions of hypervariability, are inherent to their genotype, and can be used to genotype clinical strains, separate from other genomic regions. We also show that these GAPs fall within predicted transcription factor binding sites and therefore provide targets for further functional studies.IMPORTANCEBK Polyomavirus (BKPyV) is the cause of hemorrhagic cystitis in hematopoietic cell transplant recipients and BKPyV-associated nephropathy in renal transplant recipients and thus is an important determinant of transplant outcome. The viral mechanisms leading to disease manifestation remain to be thoroughly explored, but viral genetic variation has emerged as an area of interest. Understanding genomic diversity between and within BKPyV genotypes can provide sites of interest that may ultimately improve screening strategies and provide insights into the viral factors that contribute to disease.